2020
DOI: 10.14412/2074-2711-2020-6-49-53
|View full text |Cite
|
Sign up to set email alerts
|

The use of perampanel in drug-resistant focal epilepsy: its effect on sleep

Abstract: Perampanel (PER) is an antiepileptic drug (AED), the effects of which on sleep have not been studied in Russia.Objective: to assess changes in the quality of sleep, the level of daytime sleepiness, and the polysomnographic (PSG) characteristics of nocturnal sleep in patients with drug-resistant focal epilepsy when PER is incorporated into the therapy regimen as an additional AED.Patients and methods. The investigation enrolled 12 patients (4 men and 8 women) aged 21 to 49 years with drug-resistant epilepsy tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Serving as an inhibitor of AMPA‐type glutamate receptors, perampanel (PER) has a positive effect on sleep architecture in drug‐resistant focal epilepsy. Acute adjunctive PER treatment decreased daytime sleepiness ( n = 12, 4 weeks) 30 ; chronic administration of PER had minimal influence on daytime vigilance ( n = 17, 12 weeks; n = 72, 12 weeks) 31,32 and longer‐term administration further improved daytime sleepiness ( n = 31, 24 weeks) 32 . Another study reported a 12‐week treatment of PER had no apparent effect on sleep in 10 epilepsy patients without apparent previous sleep disorders 33 .…”
Section: Anti‐seizure Medicationsmentioning
confidence: 98%
“…Serving as an inhibitor of AMPA‐type glutamate receptors, perampanel (PER) has a positive effect on sleep architecture in drug‐resistant focal epilepsy. Acute adjunctive PER treatment decreased daytime sleepiness ( n = 12, 4 weeks) 30 ; chronic administration of PER had minimal influence on daytime vigilance ( n = 17, 12 weeks; n = 72, 12 weeks) 31,32 and longer‐term administration further improved daytime sleepiness ( n = 31, 24 weeks) 32 . Another study reported a 12‐week treatment of PER had no apparent effect on sleep in 10 epilepsy patients without apparent previous sleep disorders 33 .…”
Section: Anti‐seizure Medicationsmentioning
confidence: 98%